2016
DOI: 10.1158/1078-0432.ccr-15-0987
|View full text |Cite|
|
Sign up to set email alerts
|

ROS-Induced CXCR4 Signaling Regulates Mantle Cell Lymphoma (MCL) Cell Survival and Drug Resistance in the Bone Marrow Microenvironment via Autophagy

Abstract: Purpose Patients with advanced stages of MCL have a poor prognosis after standard therapies. MCL cells in those patients often spread into tissues other than lymph nodes, such as the bone marrow. Apart from directed migration and homing, there is little understanding of the function of the CXCR4/SDF1 signaling axis in MCL. In this report, we aim to understand mechanisms of MCL cell survival in the bone marrow. Experimental Design For comprehensive analyses of MCL interactions with bone marrow stromal cells w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 54 publications
1
57
0
1
Order By: Relevance
“…Although autophagy acts as a "double-edged sword" in tumorigenesis (19), autophagy acts more as a cytoprotective mechanism in tumor therapy (20)(21)(22). Many anticancer agents, such as imatinib, cisplatin, vismodegib, and asparaginase, can also induce autophagy in tumor cells, whereas inhibition of autophagy significantly enhances the antitumor efficacies of these agents, indicating that a combination of autophagy inhibitors and antitumor agents could be an efficient therapeutic strategy for malignancy (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Although autophagy acts as a "double-edged sword" in tumorigenesis (19), autophagy acts more as a cytoprotective mechanism in tumor therapy (20)(21)(22). Many anticancer agents, such as imatinib, cisplatin, vismodegib, and asparaginase, can also induce autophagy in tumor cells, whereas inhibition of autophagy significantly enhances the antitumor efficacies of these agents, indicating that a combination of autophagy inhibitors and antitumor agents could be an efficient therapeutic strategy for malignancy (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) can lead to various effects on different signaling pathways and results in genomic instability by inducing DNA damage. ROS induces autophagy, which in turn functions in reducing oxidative damage [18,19], so the ROS level could be associated with chemoresistance and cancer stem cells [20,21,22]. ANE is reported to induce the ROS in both cancer cells and normal oral epithelial cells [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is well-accepted as a protective mechanism for cancer cells under different conditions (1720). In the present study, we found that silencing ATG5 led to undetectable TG2 levels and reduced NF-kB expression; while TG2 in turn regulated autophagy formation and flux.…”
Section: Discussionmentioning
confidence: 99%
“…It can be induced by different conditions, including nutrient deprivation/starvation, oxidative stress, hypoxia, and chemotherapeutic drugs (1720). Autophagy also plays an important role in innate and adaptive immunity and can be regulated by different cytokines, such as transforming growth factor beta (TGF-β) or IL-6 (17,2124).…”
Section: Introductionmentioning
confidence: 99%